PERSPECTIVES OF RAW MATERIALS PROVISION OF METALLURGY OF BELARUS - A. E. Nikiforov; V. M. Machulin; V. I. Gritsaenko (Литьë и металлургия, 2010)
The perspectives of raw-materials supply of metallurgy of Belarus are disclosed. It is shown that it is necessary to study the problems of development of own raw base for further reforming and development of metallurgical complex of the country.